mRNA-1273 and BNT162b2 mRNA vaccines have reduced neutralizing activity against the SARS-CoV-2 omicron variant - Edara, Venkata-Viswanadh; Manning, Kelly E.; Ellis, Madison; Lai, Lilin; Moore, Kathryn M.; Foster, Stephanie L.; Floyd, Katharine; Davis-Gardner, Meredith E.; Mantus, Grace; Nyhoff, Lindsay E.; Bechnak, Sarah; Alaaeddine, Ghina; et al. (Cell reports. Medicine, 2022)
The severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) omicron variant emerged in November 2021 and consists of several mutations within the spike. We use serum from mRNA-vaccinated individuals to measure neutralization activity against omicron in a live-virus assay. At 2–4 weeks after a primary series of vaccinations, we observe a 30-fold reduction in neutralizing activity against omicron. Six months after the initial two-vaccine doses, sera from naive vaccinated subjects show no neutralizing activity against omicron. In contrast, COVID-19-recovered individuals 6 months after receiving the primary series of vaccinations show a 22-fold reduction, with the majority of the subjects retaining neutralizing antibody responses. In naive individuals following a booster shot (third dose), we observe a 14-fold reduction in neutralizing activity against omicron, and over 90% of subjects show neutralizing activity. These findings show that a third dose is required to provide robust neutralizing antibody responses against the omicron variant. [Display omitted] •Omicron has a significant impact on vaccine-induced neutralizing antibody (nAb) titers•Naive vaccinated individuals lost nAb titers against omicron variant after 6 months•A booster (third dose) is required to maintain neutralizing activity against omicron Here in this study, Edara et al. report that 6 months after the primary series (initial two doses) of mRNA vaccination, the majority of the subjects lost detectable neutralizing antibody titers against omicron. The data suggest that a third booster dose is necessary to sustain neutralizing activity against omicron.